The Protective Effects of Saffron Stigma Alcoholic Extract against Vincristine Sulfate Drug-Induced Renal Toxicity in Rat: Saffron extract mitigate vincristine-induced renal toxicity - Beigi Harchegani, Asghar; Sohrabiyan, Milad; Bakhtiari Kaboutaraki, Hamid; Shirvani, Hossein; Shahriary, Alireza (Iranian Journal of Pharmaceutical Sciences, 2019)
Vincristine (VCR) is a potential anti-cancer drug which is highly toxic for renal tissue. This study aims to evaluate the protective effect of alcoholic extract of saffron stigma against vincristine renal toxicity in male rats. A total of 50 rats were randomly divided into 10 groups. Different doses of VCR (0.25, 0.5 and 0.75mg/kg) and saffron (0.5 and 1mg/kg) were used to treat vincristine-induced renal toxicity in rats. Serum levels of creatinine (Cr), uric acid and blood urea nitrogen (BUN) were measured using specific kits at the end of the experimental period. Serum total antioxidant capacity (TAC) and malondialdehyde (MDA) values were measured using Ferric reducing antioxidant of power (FRAP) and Thiobarbituric acid reaction (TBAR) methods, respectively. Administration of VCR caused severe renal injury with significant increase in the levels of Cr, uric acid and BUN. VCR administration (at concentration of 0.75mg/kg) significantly increased the mean level of MDA (0.51±0.021 nmol/ml; p<0.001), while TAC value was declined significantly (243.17±16.24 μmol/l; p<0.001). These effects were dose-dependently. Treatment with saffron extract decreased the level of Cr, BUN, and MDA values in VCR-exposed rats with a significant enhancement in serum TAC content. This effect was notable for rats that received 1mg/kg plant extract. Administration of saffron, especially at higher concentration, can reduce VCR-induced renal toxicity, depletion of total antioxidant and lipid peroxidation, possibly due to its antioxidative properties.